1974
DOI: 10.1002/1097-0142(197404)33:4<911::aid-cncr2820330404>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

A standard method for DNCB sensitization testing in patients with neoplasms

Abstract: A method is described for the quantification of the DNCB sensitization‐test. Sensitization was performed by epicutaneous application of 2 mg of the substance. Fourteen days later, challenges were performed by patch testing with 30, 10, and 3 μg of DNCB in acetone. In this way erroneous readings (by toxic skin responses) may be avoided. The reactions were graded according to common practice in clinical allergology (1–4+). The sum of the reactions on the three concentrations was taken as a measure of skin reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
22
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 9 publications
4
22
0
Order By: Relevance
“…Kligman & Balin (50) found that the elderly typically give much weaker reactions to DNCB. Bleumink et al (51) observed that DNCB sensitization was decreased in people over 50 years old.…”
Section: Ii) the Ability To Develop Reactivity Upon Exposure To A Newsupporting
confidence: 73%
“…Kligman & Balin (50) found that the elderly typically give much weaker reactions to DNCB. Bleumink et al (51) observed that DNCB sensitization was decreased in people over 50 years old.…”
Section: Ii) the Ability To Develop Reactivity Upon Exposure To A Newsupporting
confidence: 73%
“…Cell mediated response to dinitrochlorobenzene (DNCB) was assessed as described by Blumink et al (1974). Briefly, on day 14 of age, a primary dose (0.1 mL) of 2% DNCB in acetone was applied on 4 cm 2 area on the skin of each of the five chicks followed by a secondary dose on day 21 of the age (7 days post primary dose).…”
Section: Dinitrochlorobenzene Testmentioning
confidence: 99%
“…To monitor the delayed-type hypersensitivity reaction dinitrochlorobenzene (DNCB) test was used as explained by Blumink et al (1974). In brief, 2% DNCB dose (0.1 mL) prepared in acetone was applied on 4 cm 2 area of skin.…”
Section: Dinitrochlorobenzene (Dncb) Testmentioning
confidence: 99%